Pre-operative diagnosis of a primary uterine mature teratoma - Tzu-Chi Lin; Tze-Ho Chen; Ren-Hong Huang; Horng-Der Tsai; Ming Chen (Elsevier, 2020)
Objective: Mature cystic teratoma is a common benign ovarian tumor. But extragonadal teratomas are very rare. They mainly occur in the midline structure of the body. Uterine teratomas are extremely rare with only few reports. The diagnosis was mainly based on the operative findings. We report a case of uterine mature teratoma in a 37 year-old woman who was diagnosed before the operation. We also review the literature about this exceptional presentation. Case report: We report a case of uterine teratoma that was initially diagnosed as a uterine tumor under ultrasound examination. But teratoma was highly suspected preoperatively by the abdominal CT scan. She underwent tumor excision via laparotomy. The operative finding and the histological examination confirms the diagnosis of primary uterine teratoma. Conclusion: Preoperatively diagnosis of uterine teratoma was difficult. Although there are no gold standard to treat the uterine teratoma, the majority of the treatment choice is surgery. The prognosis of this unusual disease is relatively good in benign lesions.